1999
DOI: 10.1259/bjr.72.857.10505018
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma of the tunica vaginalis: a case with an unusually indolent course following radical orchidectomy and radiotherapy.

Abstract: Malignant mesothelioma (malignant adenomatoid tumour) of the tunica vaginalis testis is a very rare neoplasm with highly aggressive biological behaviour. Treatment is difficult, and widespread local invasion and/or metastatic disease at presentation are associated with a poor prognosis. In this case report we describe for the first time a patient who, despite presenting with locally advanced disease, remains well 10 years after diagnosis and treatment with radical orchidectomy and high dose radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Malignant mesothelioma of the tunica vaginalis is a very rare neoplasm associated with highly aggressive biological behavior. [ 6 ] It commonly occurs in elderly age group with a rapidly progressive course. Few cases have been reported in the younger age group of <25 years[ 2 ] as it was observed in the index case reported.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant mesothelioma of the tunica vaginalis is a very rare neoplasm associated with highly aggressive biological behavior. [ 6 ] It commonly occurs in elderly age group with a rapidly progressive course. Few cases have been reported in the younger age group of <25 years[ 2 ] as it was observed in the index case reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mesothelioma cells react positivelywiththrombomodulin,cytokeratin5,andcalretinin [5,[7][8][9].Theprognosisofmesotheliomaisnotaffectedbythe histologicalpattern [10],butitseemsthatthereissomeassociation between the Ki-67 index and the prognosis of the disease [11]. Mesotheliomas with low Ki-67 index seem to haveabetterprognosis [9,12,13],buttherearealsostudies thatdonotconfirmanycorrelation [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the adjuvantsetting,radiotherapyatadosageof40-60Gyisused to assure local disease control [1,8]. There are currently no guidelinesforadjuvantchemotherapyregimens.Inthisindication,manysubstanceshavebeentried.Themostcommonly used are cisplatin, pemetrexed, vinorelbin, and gemcitabine [1,4,5,10] based on regimens used for the treatment of malignantpleuralmesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Plas et al reported that the median survival period was 23 months, with a range of 2-64 months. 6 Only two of the 110 reported cases of radical orchidectomy survived more than 5 years, 7 which indicates that convalescence is very poor for this disease. Therefore, it is important to diagnose a malignant tumor as soon as possible, and then operate immediately.…”
Section: Discussionmentioning
confidence: 99%